Pengaruh Motivasi, Kompensasi Dan Disiplin Kerja Terhadap Kinerja Tenaga Kependidikan Pada Stikes Ngudi Waluyo Ungaran (Nwu) Kab. Semarang - Purwanto, Adi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2015)
The purpose of STIKES Ngudi Waluyo Ungaran is to provide services quickly, accurately, hospitality, the effectiveness of action and comfort. The performanceÂ  of employees is an important aspect of human resource management. Low performance of employees allegedly affected from several factors, including motivation, compensation and working discipline. Based on the research problem, the study aims to analyze simultaneously the influence of motivation, compensation, and working discipline to employee performance partially influence education and motivation, compensation, discipline, and work on employee performance education in STIKES Ngudi Waluyo Ungaran.The sample of this study were all employees of education as many as 35 respondents. Data collection used questionnaires, then analyzed by using multiple regression statistical test.The results show the influence of motivation, compensation, and work discipline simultaneously having an positive and significant impact toward the performance of employees of education, which means that the higher the motivation, the higher the compensation, and the higher discipline of work, the higher the performance of education employee at STIKES Ngudi Waluyo Ungaran. This shows that these variables individually can improve employee performance at STIKES Ngudi Waluyo Ungaran.